Spatz3 Adjustable Balloon: Weight Loss and Response Rates in Brazil, and how to Correctly Use the Balloon Adjustment Technique - S. A. Leonardo (Perspective of Recent Advances in Medical Research Vol. 11, 2023)
Intragastric Balloons (IGBs) have a variable and unpredictable efficacy and duration of effect. The Spatz Adjustable Intragastric Balloon (AIGB) was created to address these concerns by extending implantation to one year, reducing balloon volume for intolerance, and rising volume for reduced balloon effect. This chapter aims to determine the efficacy and response rate of the Spatz3 AIGB. The outcomes of 379 consecutive patients (pts) implanted with the Spatz3 AIGB were reviewed retrospectively (3 lost to follow up). The average BMI is 35.5, the average weight (wt) is 97.5 kg, the average excess weight is 29.1 kg, and the average balloon volume is 600ml. There were two options for balloon volume adjustments: down adjustments for intolerance and up adjustments for increased balloon effect. The average implantation time for 376 patients was 10.6 months, with a mean weight loss of 14.9 kg; 15.1% Total Body Wt Loss (%TBL) and 58% Excess Wt Loss (%EWL). Response rate (> 25%EWL) was achieved in 79% (297/376) of pts. Down adjustments in 95 pts (mean 2.4 months; mean -152.4 ml) allowed 76/95 (80%) to continue IGB therapy for at least 6 months (mean 9.1 months). Up adjustments in 205/376 (54.5%) pts (mean 5.8 months; mean + 179.2 ml) yielded additional mean wt loss of 6.5 kg. In this retrospective review of 376 Spatz3 AIGB patients, up adjustments yielded a mean 6.5kg extra wt loss for those with wt loss plateau, and down adjustments alleviated early intolerance. These two adjustment functions may have played a role in 79% of pts achieving a successful outcome (> 25% EWL). Today, in 2023, with casuistry greater than 5,000 adjustable balloons. We observed that the adjustment has a correct technique, and the use of the adjustment of the balloon with the correct orientation of the patient obtains much better results.